2022
DOI: 10.3389/fonc.2022.978671
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features, treatment, and prognosis of pregnancy-associated breast cancer

Abstract: PurposeTo identify the clinicopathological features, treatment, and prognosis of patients with breast cancer, who were diagnosed during and after pregnancy.MethodsWe searched for patients with pregnancy-associated breast cancer (PABC) using the big data query and analysis system of Peking Union Medical College Hospital from between January 1, 2013, and December 31, 2021, and matched each patient with two non-PABC patients by age at diagnosis, year at diagnosis, and tumor stage. The clinicopathologic features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…After proper adjustments, the authors found no significant differences in DFS or OS between pregnant and nonpregnant patients with breast cancer, while multivariable analyses confirmed that pregnancy was not a factor that was associated with recurrence or death risk for the pregnant subpopulation. Another recent study by Li et al [ 66 ] also demonstrated no significant difference between the EFS of patients with PABC and non-PABC patients with breast cancer ( p = 0.655). Taking all the above into consideration, it is evident that existing data are therefore not consistent, and the level of evidence from the reported results is low, given that the majority of studies are retrospective.…”
Section: Maternal Adverse Outcomesmentioning
confidence: 91%
See 1 more Smart Citation
“…After proper adjustments, the authors found no significant differences in DFS or OS between pregnant and nonpregnant patients with breast cancer, while multivariable analyses confirmed that pregnancy was not a factor that was associated with recurrence or death risk for the pregnant subpopulation. Another recent study by Li et al [ 66 ] also demonstrated no significant difference between the EFS of patients with PABC and non-PABC patients with breast cancer ( p = 0.655). Taking all the above into consideration, it is evident that existing data are therefore not consistent, and the level of evidence from the reported results is low, given that the majority of studies are retrospective.…”
Section: Maternal Adverse Outcomesmentioning
confidence: 91%
“…According to a retrospective multi-center study by Bonnier et al [ 64 ], overall 5-year recurrence-free survival, metastasis-free survival and overall survival was lower, in a statistically significant manner, for patients with PABC compared to non-PABC patients, with multivariate analysis demonstrating that pregnancy was an independent and significant adverse prognostic factor. On the other hand, an increasing number of studies are pointing towards a different direction, by presenting poorer survival outcomes for women with PABC, which, however, do not differ in a statistically significant manner from the respective outcomes of non-PABC patients, especially after adjusting the comparing groups for known prognostic factors [ 15 , 65 , 66 , 67 , 68 , 69 ]. Amant et al [ 68 ] has reported one of the largest cohort studies, which analyzed the prognosis of 311 pregnant women with PABC.…”
Section: Maternal Adverse Outcomesmentioning
confidence: 99%
“…Some authors suggest that distinguishing between breast cancer diagnosed during pregnancy and postpartum/lactation could improve the characterization of disease biology and prognosis [9]. In fact, PABC and post-partum BC might present different clinical characteristics [10], and data on prognosis are still highly controversial [11,12]. Lastly, one study focused on differences among PABC diagnosed in different trimesters of gestation, and found better clinicopathological characteristics and prognosis in first-trimester PABC [13].…”
Section: Introductionmentioning
confidence: 99%